On the completeness of the β→ω transformation in metastable β titanium alloys. Issue 1 (7th February 2017) - Šmilauerová, Jana; Harcuba, Petr; Kriegner, Dominik; Holý, Václav
Abstract : The degree of completeness of the β→ω transformation in a metastable β titanium alloy has been determined by X‐ray diffraction. Abstract : The completeness of the β→ω transformation in ω particles in a Ti–8 at.%Mo (Ti–15 wt%Mo) single crystal was investigated by measuring the X‐ray diffraction maximum, which is forbidden in both the pure body‐centred cubic β phase and the hexagonal ω phase, and also the diffraction maxima 0001, 0002 and, which are forbidden in the β phase and allowed in ω. From a comparison of the integrated intensities and widths of the diffraction peaks with simulations, the effective (mean) degree of the transformation was determined and the radial profile of the transformation degree in an ω particle was estimated.